High-efficiency microcrystalline silicon solar cells on honeycomb textured substrates grown with high-rate VHF plasma-enhanced chemical vapor deposition. (7th July 2015) - Sai, Hitoshi; Maejima, Keigo; Matsui, Takuya; Koida, Takashi; Kondo, Michio; Nakao, Sachiko; Takeuchi, Yoshiaki; Katayama, Hirotaka; Yoshida, Isao
Abstract: The potential of high-rate growth of high-quality microcrystalline silicon (µc-Si:H) films for solar cell applications is investigated by very high frequency plasma-enhanced chemical vapor deposition (VHF-PECVD) under a high-pressure SiH4 depletion condition. It is found that the morphology of textured substrates plays an important role in not only light trapping but also µc-Si:H film growth. A high conversion efficiency of 11.1% is attained in a substrate-type µc-Si:H cell on a substrate with honeycomb textures, which has rounded concaves in a honeycomb arrangement with an appropriate period. It is also clarified that ZnO:B films grown by metal organic chemical vapor deposition (MOCVD) are beneficial in terms of carrier collection compared with the standard In2 O3 :Sn (ITO) film grown by sputtering. On the basis of these findings, a new world-record µc-Si:H cell with a certified conversion efficiency of 11.8% is developed with a relatively high deposition rate of 1 nm/s.